Otimização do posicionamento de concentradores GPRS em redes elétricas inteligentes utilizando programação linear e teoria de filas - Souza, Gustavo Batista de Castro (2014)
Smart Grids systems have become widespread around the world. The RF mesh communication systems have contributed to make power systems smarter and reliable with implementation of Distributed Automation and Demand Response technologies. This work presents a methodology for positioning of GPRS concentrators in a energy meter ZigBee mesh network in order to attain the average network delay, thus aiming to improve the performance of the communication service. The proposed algorithm determines the amount and placement of concentrators using Integer Linear Programming and a Queuing Model for the Mesh Network. The solutions given by the proposed algorithm are validated by verifying the network performance through computer simulations based on real network scenarios.